Corruption and Government Mechanisms In Nigeria: Diagnosis And Treatment - Dauda, Muritala (Journal of Techno-Social, 2022)
Is widely perceived by many that corruption and other unethical conduct have become a destructive cankerworm that has eaten deep into every nation's economy. Although the scenario is not common only in Nigeria, the manner in which the ill-gotten wealthy individuals were being celebrated in the country is highly alarming. Nigeria is known for its series of anti-corruption mechanisms put in place by the government in order to curtail the menace in society. Upon the establishment of the Military Legislations to curb the menace in 1975 under Generals Murtala Ramatu Muhammed and Olusegun Obasanjo down to 1999 under the administration of President Olusegun Obasanjo where two separate anti-corruption bodies were formed (ICPC and EFCC), and to the present Administration under President Muhammadu Buhari where whistleblowing mechanism is introduced, the level of corruption is more pronounced and rampant both in public and private sectors of the Nigeria’s economy. One will be wondering why Nigeria is yet to put total remedies to the scourge of corruption in the country. The study proffers some hints if it can be adopted by the government to strengthen the anti-corruption tools put in place. Some of the measures include the inclusion of individuals, all and sundry in the fight against corruption. As opined by the collective action theory employed by the study, corruption cannot be fought and won in isolation but requires collective efforts and change of masses’ orientation on the need to return sanity back to Nigeria. Similarly, our religious and traditional leaders have numerous roles to play in reducing unethical conduct in society. Conferment of religious or traditional titles to those that do not deserve it in society should be corrected and discouraged in its totality. When these and many more are done, there is every possibility that Nigeria will be a lesser corrupt country and great again.Keywords: Nigeria, EFCC, Whistle-blowing, Corruption, Unethical Conducts,